2015
DOI: 10.1002/cncr.29622
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 study of sunitinib in patients with metastatic mucosal or acral melanoma

Abstract: BACKGROUND:Patients with mucosal and acral melanomas have limited treatment options and a poor prognosis. Mutations of the KIT oncogene in these melanoma subtypes provide a potential therapeutic target. METHODS: A multicenter phase 2 trial of sunitinib was conducted in patients with unresectable stage III or IV melanoma of a mucosal or acral primary origin. Patients were treated in 2 cohorts: cohort A received sunitinib at a dose of 50 mg daily for 4 weeks of a 6-week cycle, and cohort B received sunitinib at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Additionally, a Phase II trial of sunitinib, a multi-targeted receptor tyrosine kinase inhibitor, was performed in patients with stage III or IV metastatic AM. Although the medication was poorly tolerated, sunitinib Improving the diagnosis & treatment of acral melanocytic lesions REVIEW future science group www.futuremedicine.com showed short-term activity in the treatment of AM that was not dependent on the presence of KIT mutations [82].…”
Section: • • Systemic Therapiesmentioning
confidence: 99%
“…Additionally, a Phase II trial of sunitinib, a multi-targeted receptor tyrosine kinase inhibitor, was performed in patients with stage III or IV metastatic AM. Although the medication was poorly tolerated, sunitinib Improving the diagnosis & treatment of acral melanocytic lesions REVIEW future science group www.futuremedicine.com showed short-term activity in the treatment of AM that was not dependent on the presence of KIT mutations [82].…”
Section: • • Systemic Therapiesmentioning
confidence: 99%
“…Multi-kinase inhibitors targeting mainly FLT3 are generally accepted for acute myeloid leukemia (AML) treatment but are not clinically used on solid tumors due to low efficacy. Currently, combination treatments, instead of single therapeutic agents, are being extensively investigated for the treatment of solid tumors [9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…for treating advanced renal cell carcinoma, imatinib-resistant, or intolerant gastrointestinal stroma tumor (GIST), and advanced pancreatic neuroendocrine tumors [ 1 ]. Recent studies have reported that sunitinib controls c-KIT or non c-KIT mutated malignant melanoma (MM) [ 2 6 ]. However, sunitinib is not clinically widely used on solid tumors due to the low efficacy [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that sunitinib controls c-KIT or non c-KIT mutated malignant melanoma (MM) [ 2 6 ]. However, sunitinib is not clinically widely used on solid tumors due to the low efficacy [ 6 9 ]. How to improve the efficacy of sunitinib in solid tumor remains a big challenge for oncologists’ world widely.…”
Section: Introductionmentioning
confidence: 99%